Jhāṛakhaṇḍera lokasāhitya - Māhāta, Baṅkimacandra, 1938- (Pratima Prakāśana ; paribeśanāẏa, Ḍi.Ema. Lāibrerī, 1978)
Study on the folk literature of Jharkhand, area in southwestern Bengal and adjoining portions of Orissa and Bihar.